Decoupling in Argumentation: Toulmin’s intuitive loop (ALPHA. Journal of Arts, Literature and Philosophy, 2019)
In this paper, I propose to understand argumentative decoupling, that is, the structural fact of presenting something as data in one argument and then the same information as a conclusion in another argument, as the decoupling of representations. To achieve this approach, I discuss perspectives from cognitive and evolutionary theories that describe this phenomenon in intentional communication in other species, as well as in human infants. I conclude by discussing the relationship between this human cognitive capacity and the problem of reflexivity.
Keywords: Argument; decoupling; reflexivity; Toulmin